AKTUALISASI PENDIDIKAN KARAKTER BERBASIS PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DALAM KURIKULUM SMP - Nurul Qomaria, Elysa (ILJ: Islamic Learning Journal, 2024)
This study examines the actualization of character education based on Islamic Education (PAI) and moral values within the 2013 Curriculum at SMP A. Wahid Hasyim. The focus of the research includes the variety of character education, the techniques of actualization, as well as supporting and inhibiting factors. Using a qualitative approach with a case study design, data were collected through interviews, observations, and documentation. The findings reveal that values such as spirituality, honesty, and responsibility are integrated through the curriculum, classroom teaching, and new subjects. Supporting factors include the school environment and the adiwiyata program, while obstacles arise from collective student issues and a lack of parental involvement. Efforts to overcome these obstacles include the implementation of punishments, guidance, and teacher motivation.